Plastic-to-fuel: effect of nickel and cerium - Ruzinah, Isha; Najwa, Mohd Nor; Fun Win, Fan; Ali Zaynal Abidin, Othman; Mohd Ali, Mohd.Kucheb; Muhamad Nurfaiz, Azmy; Hafizah, Ramli; Siti Hajar Noor, Shaarani; Norazana, Ibrahim; Nooryusmiza, Yusoff (Universiti Malaysia Pahang, 2018)
nvestigation on converting waste including plastic waste; one of major waste compositions, via pyrolysis is recently explored by many researchers. One of the goal of the current researches is to develop a lower cost of catalyst. However, low yield and fuel quality are among major obstacles to scale up this process. The aim of this paper is to synthesis, characterize and study the performance of the catalysts with nickel or cerium metal loading on oil palm ash catalyst for plastic to fuel via catalytic pyrolysis. The High Density Polyethylene (HDPE) resin was used and thermally characterized with TGA. A 20 wt% of metal in nickel/ash or cerium/ash catalysts were synthesized via wet impregnation. The fresh catalysts were characterized via BET and SEM analysis.